Dangerous fields: Existentiality, humanity and musical creativity in German refugee camps. Issue 2 (October 2020) - Pistrick, Eckehard
This article focuses on the role of music in the context of humanitarian and existential crisis. It argues that the ethnographic field of the refugee camp is everything else than an unproductive space, a "waiting room" of the undesirables, an in-between space where social lives are suspended and where cultural life ceases to exist. It presents in a first part the particular spatial and temporal dimensions of a specific refugee reception center in Germany, in which the author has both volunteered for 6 months organizing music room sessions, and in which he has worked as an engaged anthropologist in the framework of a 4-month grassroots music theater project. In a second part, individual biographies of musicking asylum-seekers are presented: seen from the standpoint of an anthropology of emotions and an anthropology of absence, it will be discussed in which way the experience of marginalization, social exclusion and continuous waiting has influenced the texts and musical pieces created by them. In more general terms, this article looks at the ethnomusicologists' dilemma of whether and how to make visible and audible such cultural creativity in an empathetic way without detaching it from the precarious and existential situations under which it unfolds.